A statistical quality control study on Jollibee Foods Corporation - Manuel, Catherine Marie; Mape, Aristotle; Tanyu, Katherine Mae (Quezon City College of Engineering, University of the Philippines Diliman, 2006)
A statistical quality control study is done on Jollibee Foods Corporation's central commissary. Amidst the various products of the fast-growing fast-food chain, the group focused on the company's bun line. A Pareto chart of defects is constructed to check what the defects that mainly affect buns are. Majority of the errors take place in terms of bun height. Afterwards, an Ishikawa diagram is constructed as a tool to help trace the assignable causes to the possible outliers. After establishing the normality of the data, the R-charts and Xbar-charts aim to eliminate the out-of-control points that hinder the stability of the process. Most of the out-of-control points are attributed to machine jams and thus machine downtime. The capability of the process is analyzed to check whether the buns fall within the specifications limits. It is found out that the process is not centered and that a number of the buns (in PPM) do not comply with the height specifications. From studying the efficiency reports of various production days, the group recommends that Jollibee Foods Corporation highly invest in maintenance of the equipment. This is partly common sense as the bun line itself is automated. However, by studying the times when the specific machine downtimes occurred, management could seek to prevent the machine jams from occurring. Also, by knowing the most frequent machine problem, management could seek to focus more on the specific portion of machine failure. This would be an interesting area of study.
Submitted in partial fulfillment of the course requirements in IE 135 : Industrial quality control.
Keywords: Jollibee Foods Corporation; Fast food restaurants; Quality control